INTERCOUNTRY SURROGACY: AN ITALIAN AND UKRAINIAN ISSUE - Long, Joëlle (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The present analysis is based on a survey of Italian jurisprudence (period 1989-2016) that identifies sixteen cases arising from surrogacy arrangements undertaken by people living in Italy and highlights that nine of them involve Ukraine as country of origin. Since all Italian couples were acquitted in criminal proceeding, it is argued that the real sanction against surrogacy is the denial of civil effects in Italy. This paper will therefore focus on private international law and family law issues related to surrogacy and offer some reflections on the lights and shadows of the use of the principle of the best interest of the child to legitimate «procreative tourism». To conclude, I will advocate the need for a dialogue between the countries of origin and the receiving countries involved in surrogacy in order to define shared substantive and procedural guarantees.